The Ideology of Work : Theoretical Humanism, Work and Labour - Mercer, Samuel J.R. (Historical Materialism Book Series, 2024)
In On the Reproduction of Capitalism , Louis Althusser cited an appendix which, it seems, remains lost or was never completed. This appendix was titled 'the Ideology of Work'. This book takes inspiration from this appendix, to think about what is at stake for both Marxism and sociology in analysing work from an Althusserian perspective today. The dominant form of this ideology of work today is theoretical humanism. This book demonstrates how theoretical humanism has undermined the analysis of work and makes the case for a Marxism in sociology with a committed theoretical anti-humanism at the forefront of its endeavour.